2019
DOI: 10.1007/s13197-019-03778-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ageing on longissimus lumborum quality from Holstein-Friesian young bulls fed different diets

Abstract: The aim of the study was to investigate the effect of ageing (9 and 14 days) on beef obtained from Polish Holstein-Friesian bulls (n = 24) fed different dietary treatments containing the addition of herbal preparations (treatments: control, one and two herbal preparations). Between the 9th and 14th day of ageing, moisture and expressible water contents, Warner–Bratzler Shear Force (WBSF) and intensity of untypical taste significantly decreased, whereas redness, yellowness, chroma, intensity of meat aroma and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Therefore, beef producers have difficulties in offering the meat with consistent quality traits (tenderness, juiciness and taste) to consumers. The improvement of the beef quality and its repeatability is the aim of studies conducted by many research groups in Poland and all over the World (Isleroglu, Kemerli, & Kaymak-Ertekin, 2015;Lizaso, Beriain, Horcada, Chasco, & Purroy, 2011;Macharáčková et al, 2021;Modzelewska-Kapituła, Tkacz, Nogalski, Karpińska-Tymoszczyk, & Więk, 2019;Supaphon et al, 2021;Węglarz, 2010;Wyrwisz et al, 2016;Yang et al, 2021). The issue is of vital importance because of recent trends in meat consumption where price will be not the most important factor for purchasing, whereas high and repeatable quality (nutritional value, sensory, and hygienic quality) is going to be the most important (Henchion, McCarthy, Resconi, & Troy, 2014;Listrat et.al., 2020a;Żakowska-Biemans et.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, beef producers have difficulties in offering the meat with consistent quality traits (tenderness, juiciness and taste) to consumers. The improvement of the beef quality and its repeatability is the aim of studies conducted by many research groups in Poland and all over the World (Isleroglu, Kemerli, & Kaymak-Ertekin, 2015;Lizaso, Beriain, Horcada, Chasco, & Purroy, 2011;Macharáčková et al, 2021;Modzelewska-Kapituła, Tkacz, Nogalski, Karpińska-Tymoszczyk, & Więk, 2019;Supaphon et al, 2021;Węglarz, 2010;Wyrwisz et al, 2016;Yang et al, 2021). The issue is of vital importance because of recent trends in meat consumption where price will be not the most important factor for purchasing, whereas high and repeatable quality (nutritional value, sensory, and hygienic quality) is going to be the most important (Henchion, McCarthy, Resconi, & Troy, 2014;Listrat et.al., 2020a;Żakowska-Biemans et.…”
Section: Introductionmentioning
confidence: 99%
“…The needed ageing time for a given tenderness may be affected by the feeding system. In a study where it was assessed the influence of ageing on longissimus lumborum of Polish Holstein-Friesian bulls, animals were fed with different dietary treatments containing none, one or two herbal preparations (Optirum and Stresomix), and it was concluded that using two herbal preparations in the animal diet reduced the time of ageing from 14 to 9 days to obtain similar tenderness, compared to animals fed without the herbal supplements (Modzelewska-Kapituła et al, 2019). Authors suggested that this faster tenderization of meat from animals fed with two herbal preparations could be due to the higher antioxidants in meat that can inhibit the oxidation of protein resulting in tender meat (Modzelewska-Kapituła et al, 2019).…”
Section: D) Ageing and Ageing Timementioning
confidence: 99%
“…Although its importance depends on various factors, tenderness has been identified as the most important factor of palatability in several studies [ 19 , 20 , 21 ], and recent investigations have most commonly shown flavor to be the largest factor impacting overall beef eating satisfaction [ 22 , 23 , 24 ]. Both traits are influenced by intrinsic and extrinsic factors, among which diet [ 25 , 26 , 27 , 28 ] and aging [ 29 , 30 , 31 , 32 , 33 ] are notable. The animal feed affects the hygienic, sanitary, nutritional, and sensory characteristics of meat.…”
Section: Introductionmentioning
confidence: 99%